North-to-South Transport Service Modes of Power Coal Based on Bi-level Programming Game Model: A Comparative Study on Inner Mongolia-Jiangxi Railway and Shipping Services - Liang, Shuqi (Journal of coastal research, 2019)
Liang, S.-Q., 2019. North-to-South transport service modes of power coal based on bi-level programming game model: A comparative study on inner Mongolia-Jiangxi railway and shipping services. In: Gong, D.; Zhu, H., and Liu, R. (eds.), Selected Topics in Coastal Research: Engineering, Industry, Economy, and Sustainable Development. Journal of Coastal Research, Special Issue No. 94, pp. 460–464. Coconut Creek (Florida), ISSN 0749-0208. The coal transport mode from North to South China is investigated to find out how the ocean shipping mode and the north-to-south coal transport are susceptible to the Inner Mongolia-Jiangxi railway based on the bi-level programming game model. This paper derives the following conclusions from the case analysis of the competitive behaviors for the Erdos-Wuhan transport service modes: (1) The inauguration of Inner Mongolia-Jiangxi Railway has obvious traffic transfer effect on the traditional sea-railway combined transport mode, and will lead the freight rate to further reducing; (2) the higher the value of time (VOT) in coal transport service, the more apparent the competition effect of Inner Mongolia-Jiangxi Railway on sea-railway combined transport service mode; (3) the upgrading of sea-railway combined transport service level, especially its rapidity and punctuality, has regulation effect on the competition of Inner Mongolia-Jiangxi Railway. In the end, this paper gives some policy advice on how to improve the transport efficiency of coal from north to south China subject to freight rate, service upgrading and marketing strategies.